K-shell photoionization of O4 + and O5 + ions: experiment and theory. Issue 4 (22nd November 2016) - McLaughlin, B. M.; Bizau, J.-M.; Cubaynes, D.; Guilbaud, S.; Douix, S.; Shorman, M. M. Al; Ghazaly, M. O. A. El; Sakho, I.; Gharaibeh, M. F.
Abstract: Absolute cross-sections for the K -shell photoionization of Be-like (O 4 + ) and Li-like (O 5 + ) atomic oxygen ions were measured for the first time (in their respective K -shell regions) by employing the ion–photon merged-beam technique at the SOLEIL synchrotron-radiation facility in Saint-Aubin, France. High-resolution spectroscopy with E /Δ E ≈ 3200 (≈170 meV, full width at half-maximum) was achieved with photon energy from 550 to 670 eV. Rich resonance structure observed in the experimental spectra is analysed using the R-matrix with pseudo-states (RMPS) method. Results are also compared with the screening constant by unit nuclear charge (SCUNC) calculations. We characterize and identify the strong 1s → 2p resonances for both ions and the weaker 1s → n p resonances ( n ≥ 3) observed in the K -shell spectra of O 4 + .